Bone Disease Diagnosis Expert System (Orthopedics) Using Forward Chaining Method - Siti Hartini; Roy Fanry Siahaan (Putaka Timur Publisher, 2021)
Diseases or disorders of the bones can occur due to various things. One of them is a broken bone caused by an accident. There are also bone abnormalities that occur due to infection, joint disorders, attitude errors, and physiological disorders. However, many people do not realize the early symptoms of the bone disease they are experiencing so that the disease becomes more severe. Moreover, people's knowledge is minimal about the bone disease. Therefore, an Expert System is needed which aims to diagnose diseases of human bones to help patients to get early treatment of the disease they are experiencing. To overcome the problems described above, one of them is by building an expert system. With the help of computer technology, this expert system is expected to help make it easier to diagnose the symptoms of bone disease. To diagnose bone disease, this expert system uses the Forward Chaining method by entering disease data and symptoms. So that this expert system can make it easier for users to get information about symptoms and bone diseases. So that it can help the community in finding suggestions and solutions for bone diseases.